2012
DOI: 10.1103/physreva.85.022901
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-assisted electron-electron collisions at metallic surfaces

Abstract: We present a theoretical treatment for the ejection of a secondary electron from a clean metallic surface induced by the impact of a fast primary electron. Assuming a direct scattering between the incident, primary electron and the electron in a metal, we calculate the electron-pair energy distributions at the surfaces of Al and Be. Different models for the screening of the electronelectron interaction are examined and the footprints of the surface and the bulk plasmon modes are determined and analyzed. The fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…[14][15][16][17][18] Further studies revealed the role of the surface dielectric response on the correlated pair emission. [19][20][21][22] For a fast incoming electron (>100 eV) and a small energy and momentum loss (i.e., for a small momentum transfer) of this electron the pair-correlation technique delivers related spectroscopic information as done by the angle-resolved photoemission spectroscopy (ARPES) 23,24 (using linearly polarized photons). For the pair emission technique however, electronic transitions with a large wave vector change can be induced at moderate impact energy.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Further studies revealed the role of the surface dielectric response on the correlated pair emission. [19][20][21][22] For a fast incoming electron (>100 eV) and a small energy and momentum loss (i.e., for a small momentum transfer) of this electron the pair-correlation technique delivers related spectroscopic information as done by the angle-resolved photoemission spectroscopy (ARPES) 23,24 (using linearly polarized photons). For the pair emission technique however, electronic transitions with a large wave vector change can be induced at moderate impact energy.…”
Section: Introductionmentioning
confidence: 99%
“…The longitudinal excitation spectra of allowable modes will be determined from a knowledge of the frequencydependent non-local dielectric function (r, r ; ω) of the composite system, which depends on the position coordinates r, r and frequency ω. Alternatively, the normal modes correspond to the resonances of the inverse dielectric function K(r, r ; ω) satisfying dr K(r, r ; ω) (r , r ; ω) = δ(r − r ). The significance of K(r, r ; ω) is that it embodies manybody effects 31,32 through screening by the medium of an external potential U (r ; ω) to produce an effective potential V (r; ω) = dr K(r, r ; ω)U (r ; ω). In Sec.…”
Section: Recent Research On Plasmon Excitationsmentioning
confidence: 99%
“…These findings show that for a material with a complex band structure, such as graphite, the excitation of a plasmon and the associated interband transitions are both essential parts of the same coherent process, a plasmonassisted interband transition [50] leading to ejection of the bound electron into an excited state. This picture supports the momentum-exciton model for the plasmon [25,51] as a coherent excitation of a (rather small) number of electron hole pairs behaving as a quasi-particle with a well-defined energy and momentum.…”
mentioning
confidence: 82%